Development of staff information-communication environment for State organization National Antarctic scientific center - Y. I. Fedyay; R. L. Novogrudskaya (Ukrainian Antarctic Journal, 2016)
The work is dedicated to improve the efficiency of interaction of employees of the State organization National Antarctic scientific center (SO NASC), through the development of information-communication environment. The review of information and communication environments for various activities and analyzes the main elements of such environments. Based on comparative analysis the structure of information-communication environment of SO NASC was proposed, describes the elements of the environment, depending on the scope of employee designed the layout of the environment.